Strategi Peningkatan Profitabilitas Warung Bakso Mie Ayam: Analisis Keuangan dan Pengelolaan Kerugian - Eniawati Laia; Alleta Dewi Maria (Mahesa Research Center, 2024)
This article aims to analyze the financial management of Warung Bakso Mie Ayam Pak Tukul and seek solutions to enhance the business's profitability. The focus is on the constraints in cost control and irregular financial recording, which lead to uncertainty in financial performance. To address this issue, relevant financial management and accounting theories are used, including cost control principles and effective accounting practices. Data were collected through direct observation and semi-structured interviews with the owner and employees. Observations focused on operational processes, inventory management, and financial recording practices, while interviews included questions about the challenges faced and strategies implemented. The analysis results indicate that the warung experiences significant income fluctuations and losses in certain months, due to the lack of an effective cost control system and irregular financial recording.This study concludes that the implementation of a simple accounting system and tighter cost control can help improve financial conditions. Additionally, menu diversification by adding new options, such as bundling discounts and cost-effective digital promotions, along with risk analysis related to the implementation of these new strategies, can help enhance profitability sustainably.